PERAN MEDIA DIGITAL DALAM PROMOSI PARIWISATA OLEH PEMERINTAH INDONESIA (STUDI PADA BEBERAPA WEBSITE PEMERINTAH INDONESIA) - Retno Yulita; Suprihatin Ali; Fenny Saptiani (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Tourism destinations managed by each Tourism Department in Indonesia really need to be promoted by utilizing digital media in order to attract more consumers and increase the number of visits. Promotion plays an important role in tourism marketing which will have an impact on the national economy. The purpose of this study was to determine the role of digital media in tourism promotion by the Indonesian government. This research is a type of qualitative research with a case study approach. Based on the source, the type of data used in this study is secondary data, namely the official websites of 34 Provincial Tourism Department in Indonesia. Data collection techniques were carried out in two ways, namely non-participant observation and documentation. The results of this study indicate that the sequence of digital media most used by the Provincial Tourism Department in tourism promotion is website, Youtube, Facebook, Instagram, Twitter, and Tiktok. Then there are several forms of promotion through digital media carried out by the Provincial Tourism Departments in Indonesia, namely optimizing website content and social media; compiling e-book and calendar of events; promotions through talk shows, podcasts, web series or films; as well as offering tour packages. It is hoped that the Provincial Tourism Department can strengthen synergy with the community and business actors in tourism development, especially in tourism promotion by utilizing digital media so that it can reach more potential visitors.